Associação do consumo alimentar e composição corporal com a gravidade de migrânea, antes e após intervenção nutricional - Aline Barbara Pereira Costa (2013)
Introduction: Migraine is a common, painful and disabling disorder. The ingestion of certain foods by susceptible people is one of the hypotheses related to this disease. Obesity is another factor that has been linked to migraine, exerting influence on the increased prevalence, severity and chronicity of this condition. Objective: To evaluate the association between body composition and food intake with the migraines severitybefore and after dietary intervention. Methods: Non-Randomized and non-controlled intervention, developed over three months, with migraneurs 18 or older. Before the intervention patients underwent indirect calorimetry, anthropometric and body composition assessment (measurement of weight, height, waist and hip circumferences and bioelectrical impedance analysis), dietary evaluation (24 hour recall and the Brazilian Healthy Eating Index Revised BHEI-R adapted), severitys migraine assessment (by using the Migraine Disability Assessment - MIDAS and the Headache Impact Test - HIT-6) and depression symptoms evaluation (by using the Beck Depression Inventory BDI). We also investigated the perception triggers of migraine attacks. All subjects received diets consistent with the initial nutritional diagnosis, and counseling on healthy eating and healthy lifestyle. Every 30 days the patients were reassessed to identify changes in anthropometric parameters, dietary intake and severity of attacks. Results: Fifty two women were evaluated and had on average 44.4 ± 13 years old and a high frequency of excess of adiposity: 61.5% were overweight and had increased visceral fat and 63.6% were at risk for developing obesity-related diseases. Twenty-seven associated the onset of seizures patients with some food intake. Migraine crises exerted severe impact on the lives of 66.7% of patients and 46% reported moderate to severe disability due to headache. Patients with chronic migraine had a higher body fat percentage (p = 0.024), increased resting energy expenditure (p = 0.008) and worse scores of the HIT-6 (p = 0.000) and MIDAS (p = 0.001). The dietary assessment showed low mean score of BHEI-R adapted (61,2 ± 12,31), and high frequencies of insufficient intake of calories (77%), fiber (85%) and polyunsaturated fatty acids (63 %), and the excessive consumption of saturated fatty acids (35%). After dietary intervention there was a reduction in weight and BMI after 30 days,improvements in BDI and BHEI-R adapted scores after 60 days and improvement in the HIT-6 score after 90 days (p 0.05). Conclusion: The highest degree of adiposity was related to chronic migraine. In addition, the nutritional intervention was able to promote improvements in anthropometric and dietary patterns, reflecting on the reduction of headaches severity of women suffering from migraine.